Generation of a helper phage for the fluorescent detection of peptide-target interactions by dual-display phages - Laura Maria De Plano; Salvatore Oddo; Salvatore P. P. Guglielmino; Antonella Caccamo; Sabrina Conoci (Scientific Reports, 2023)
Abstract Phage display is a molecular biology technique that allows the presentation of foreign peptides on the surface of bacteriophages. It is widely utilized for applications such as the discovery of biomarkers, the development of therapeutic antibodies, and the investigation of protein–protein interactions. When employing phages in diagnostic and therapeutic monitoring assays, it is essential to couple them with a detection system capable of revealing and quantifying the interaction between the peptide displayed on the phage capsid and the target of interest. This process is often technically challenging and costly. Here, we generated a fluorescent helper phage vector displaying sfGFP in-frame to the pIII of the capsid proteins. Further, we developed an exchangeable dual-display phage system by combining our newly developed fluorescent helper phage vector with a phagemid vector harboring the engineered pVIII with a peptide-probe. By doing so, the sfGFP and a peptide-probe are displayed on the same phage particle. Notably, our dual-display approach is highly flexible as it allows for easy exchange of the displayed peptide-probe on the pVIII to gain the desired selectivity, while maintaining the sfGFP gene, which allows easy visualization and quantification of the interaction peptide-probe. We anticipate that this system will reduce time and costs compared to the current phage-based detection systems.